Revisiting the Principles of Preservation in an Era of Pandemic Obesity - Langford, John T.; DiRito, Jenna R.; Doilicho, Natty; Chickering, Graylen R.; Stern, David A.; Ouyang, Xinshou; Mehal, Wajahat; Tietjen, Gregory T. (Frontiers in Immunology, 2022)
The current obesity epidemic has caused a significant decline in the health of our donor population. Organs from obese deceased donors are more prone to ischemia reperfusion injury resulting from organ preservation. As a consequence, these donors are more likely to be discarded under the assumption that nothing can be done to make them viable for transplant. Our current methods of organ preservation—which remain relatively unchanged over the last ~40 years—were originally adopted in the context of a much healthier donor population. But methods that are suitable for healthier deceased donors are likely not optimal for organs from obese donors. Naturally occurring models of acute obesity and fasting in hibernating mammals demonstrate that obesity and resilience to cold preservation-like conditions are not mutually exclusive. Moreover, recent advances in our understanding of the metabolic dysfunction that underlies obesity suggest that it may be possible to improve the resilience of organs from obese deceased donors. In this mini-review, we explore how we might adapt our current practice of organ preservation to better suit the current reality of our deceased donor population.